China's influence and the centre-periphery tug of war in Hong Kong, Taiwan and Indo-Pacific - Fong, Brian C. H.; Wu, Jieh-Min; Nathan, Andrew J. (Andrew James) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Bringing together a team of cutting-edge researchers based in Hong Kong, Taiwan and other Asia-Oceania countries, this book focuses on the tug of war between China's influence and forces of resistance in Hong Kong, Taiwan and selected countries in the surrounding regions. China's influence has met growing defiance from citizens who fear the extinction of their valued local identities. However, the book shows that resistance to China's influence is a global phenomenon, varying in motivation and intensity from region to region and country to country depending on the forms of China's influence and the balances of forces in each society. The book also advances an integrated theoretical framework for broadly operationalizing different forms of offshore Chinese influence mechanisms, ranging from economic, military and diplomatic influences to united front operations. This book will be of key interest to scholars and students of comparative politics, international relations, geopolitics, Chinese politics, Hong Kong-China relations, Taiwan, and Asian politics"--
Re-thinking China's influence across surrounding jurisdictions : a concentric centre-periphery framework / Brian C.H. Fong -- More than sharp power : Chinese influence operations in Taiwan, Hong Kong, and beyond / Wu Jieh-min -- China's assimilation of peripheries in former Qing imperial frontiers : a comparative-historical perspective / Hung Ho-fung -- Peripheral nationalisms of Taiwan and Hong Kong under China's influence : a comparative-nationalism perspective / Wu Rwei-ren -- China's empire-building across peripheries : a comparative-imperialism perspective / Kwong Kin-ming -- China's influence on Hong Kong's elections : evidence from Legislative Council elections / Ma Ngok -- China's influence on Hong Kong's economy : lessons from mainlander tourism / Jackson Yeh -- China's influence on Hong Kong's media : subduing press freedom / Chan Chi Kit -- China's influence on Hong Kong's entertainment industry : lessons from film production / Klavier Wang -- China's influence on Hong Kong's religions : inter-religious comparison / Ying-ho Kwong -- China's influence on Taiwan's elections : the impact of the "1992 Consensus" on presidential elections / Wu Jieh-min and Liao Mei -- China's influence on Taiwan's economy : the economic statecraft of mainlander tourism / Tsai Hung-Jeng -- China's influence on Taiwan's media : A model of transnational diffusion of Chinese censorship / Huang Jaw-nian -- China's influence on Taiwan's entertainment industry : the Chinese state, entertainment capital, and netizens in the witch-hunt for "Taiwan independence suspects" / Liao Mei -- China's influence on Taiwan's religions : Mazu belief across the strait / Ku Ming-chun and Hong Ying-fa -- China's influence in Southeast Asia : no easy answers / Ian Chong -- China's influence in South Asia : under the shadow of the Sino-Indian relationship / Chietigj Bajpaee -- China's influence in Central Asia : Sinophobia and the wave of anti-China protests / Jun Kumakura -- China's influence in Australia and New Zealand : making the democratic world safe for dictatorship / Kevin Carrico and Feng Chongyi -- China's influence and the pushback : tentative conclusions beyond Hong Kong and Taiwan / Andrew J. Nathan -- The place of Hong Kong and Taiwan in the Asia policies of the Trump administration / Richard C. Bush.
OCLC-licensed vendor bibliographic record.
Keywords: China -- Relations -- China -- Hong Kong; Hong Kong (China) -- Relations -- China; China -- Relations -- Taiwan; Taiwan -- Relations -- China; China -- Relations -- Pacific Area; Pacific Area -- Relations -- China; China -- Foreign relations -- 1976-; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; POLITICAL SCIENCE / Political Freedom & Security / General